2021
DOI: 10.1097/njh.0000000000000734
|View full text |Cite
|
Sign up to set email alerts
|

Preference and Influencing Factors of Advance Care Planning for Chinese Elderly Patients With Chronic Diseases

Abstract: The incidence of chronic diseases among elderly patients increases annually with the accelerating aging process in China. Complications arising from the progression of these diseases may affect the ability of the aged to communicate and make decisions about future medical and personal care. This study aimed to investigate acceptance and influencing factors of advance care planning for community-dwelling elderly patients with chronic diseases in the Republic of China. Using a convergent parallel mixed-methods d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Factors affecting an older adult's decision to engage in ACP include age, sex, education level, health status, religious beliefs, knowledge of ACP, personal medical experience, communication with family members, support from family members, medical resources, and cultural sentiments 3,6-14 . A mixed study on older adults with chronic diseases discovered that quality of life, family support, past medical experience, and attitude toward death affected their likelihood of implementing ACP 15 . Another survey study found that the desire among older adults to reduce the burdens of surrogate decision making and older adults' negative experiences with end-of-life care were motivators for ACP 16 .…”
mentioning
confidence: 99%
“…Factors affecting an older adult's decision to engage in ACP include age, sex, education level, health status, religious beliefs, knowledge of ACP, personal medical experience, communication with family members, support from family members, medical resources, and cultural sentiments 3,6-14 . A mixed study on older adults with chronic diseases discovered that quality of life, family support, past medical experience, and attitude toward death affected their likelihood of implementing ACP 15 . Another survey study found that the desire among older adults to reduce the burdens of surrogate decision making and older adults' negative experiences with end-of-life care were motivators for ACP 16 .…”
mentioning
confidence: 99%
“…The process of communicating about one's wishes for future health care is referred to as advance care planning (ACP). Advance care planning enables patients, when conscious and capable of decision making, to rely on their life experiences and values to express their willingness to be treated and cared for when they are dying or when there is progressive deterioration of their condition beyond their control 7,8 . Advance care planning assists patients to prepare for future medical treatment and health care if and when critical illness occurs 7 .…”
mentioning
confidence: 99%
“…Generally, ACP is more prevalent in developed countries, such as North America, Australia, and New Zealand, 15-18 and more widely accepted in the medical field, particularly in hospitals, communities, and nursing homes 11,15,19 . In addition to elderly patients, the ACP population comprises parents/guardians of minors with life-threatening illnesses, with the community being extended to patients with malignant tumors, Alzheimer disease, cardiovascular, and other diseases 7,19-21 . Despite the highlighted benefits of ACP in these disease states, little research has been done on the implementation of ACP by elderly AIDS patients in China.…”
mentioning
confidence: 99%
See 2 more Smart Citations